ASSESSING THE IMPACT OF BUMDES KARYA DERMAWAN ON MAQASID SHARIA-BASED ISLAMIC ECONOMIC WELFARE: A DIFFERENCE-IN-DIFFERENCES ANALYSIS - Yogi Ahmad Yani; Muhammad Fauzi; Ahmad Yani; Agustiari (Academic Bright Collaboration, 2026)
This study aims to estimate the net impact, transmission mechanisms, and contribution of BUMDes Karya Dermawan to Maqasid Sharia-based Islamic Economic Welfare within the Dusun Dalam community. This research provides empirical evidence regarding the effectiveness of village economic institutions in enhancing both material and spiritual maslahah. This quantitative study utilizes a retrospective panel data design for the 2014–2025 period, involving 120 respondents (60 in the treatment group and 60 in the control group) selected via purposive sampling. The study explicitly acknowledges the potential for recall bias due to the retrospective nature of the survey, which was mitigated through data triangulation with village documentation. Data analysis was conducted using Difference-in-Differences (DiD) regression and Independent Sample t-test. The findings indicate a significant estimated net impact (DiD) of 8.064 (sig. 0.000) and a corrected post-intervention mean welfare difference of 5.969 (sig. 0.000) between the two groups. The transmission mechanisms identified through qualitative field observations occur through the Savings and Loans unit (functioning as qardhul hasan), agricultural machinery (Alsintan), and agricultural production facilities (Saprodi). The employment variable is proven to be the primary determinant in community welfare improvement. This study recommends strengthening the legal aspects of BUMDes business units by formalizing them into a certified Sharia-compliant system. The primary limitations of this study lie in its reliance on retrospective recall data and its restricted geographical scope. The primary value of this study lies in the application of a retrospective panel DiD framework over an 11-year horizon (2014–2025) to evaluate BUMDes performance through a holistic Maqasid Sharia lens, providing a more rigorous and balanced framework for assessing community-based economic empowerment.